Evaluation of Terlipressin’s Therapeutic Efficacy and Safety Profile in the Management of Intestinal Paralysis Among End-stage Liver Disease Patients - Muhammad Amjad Khan, Faisal Nabi Depar, Shafaq Farooq, Sadaf Yousaf, Ayesha Samad Dogar, Niaz Ahmed (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Intestinal paralysis is a common yet under-recognized complication in patients with end-stage liver disease (ESLD), leading to increased morbidity and hospital stay. Objective: To evaluate the therapeutic efficacy and safety profile of Terlipressin in the management of intestinal paralysis among ESLD patients. Methods: This prospective, observational study was conducted at Department of Gastroenterology Muhammad Teaching Hospital Peshawar during august 2021 to January 2023. A total of 52 adult patients (aged ≥18 years) with a confirmed diagnosis of end-stage liver disease and clinical features suggestive of intestinal paralysis were enrolled in the study. All patients received intravenous Terlipressin at a dose of 1 mg every 6 hours. The treatment duration ranged from 48 to 96 hours, adjusted based on individual clinical responses. The drug was administered under inpatient care with continuous monitoring of hemodynamic and renal parameters. Results: The mean time to return of bowel sounds was 27.4 ± 9.2 hours, and spontaneous bowel movement occurred within 48 hours in 84.6% of patients. Abdominal distension resolved in 88.5%, and 78.8% tolerated oral intake by Day 4. Significant reductions were observed in abdominal girth (p < 0.001) and serum creatinine (p = 0.042), with a modest drop in serum sodium (p = 0.032). Minor adverse effects occurred in 17.3% of patients, with no major ischemic or cardiac events. Clinical success was achieved in 92.3% of cases without the need for surgical intervention. Conclusion: It is concluded that Terlipressin offers a promising and safe therapeutic option for managing intestinal paralysis in ESLD patients. Its use is associated with early symptom resolution and improved clinical outcomes, warranting further investigation in larger, controlled trials. Keywords: End Stage Liver Disease, Intestinal Paralysis, Terlipressin